2017
DOI: 10.1007/s40069-017-0216-5
|View full text |Cite
|
Sign up to set email alerts
|

Freeze–Thaw Resistance and Drying Shrinkage of Recycled Aggregate Concrete Proportioned by the Modified Equivalent Mortar Volume Method

Abstract: To evaluate the effect of the mix proportioning method on drying shrinkage and freeze-and-thaw resistance of recycled concrete aggregate (RCA) concrete, two series of concrete mixes were made using the modified equivalent mortar volume (EMV) method and the conventional ACI method. In this study, different sources of RCAs were manufactured from on-site plants on air bases and at a commercial recycling plant. Keeping the total mortar at the same level, concrete mixes were proportioned by the modified EMV method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…It should be noted that all RCAs did not meet the specified Korean standards (KS) for concrete with respect to 2.5 as the specific gravity and 3.0% as water absorption, except for the 'RA' aggregate, which marginally satisfied the specific gravity standard with a value of 2.52 [35][36][37][38]. Previous studies have mainly focused on obtaining test results for the elastic modulus [5,8,12,13,27,28] and drying shrinkage [28][29][30] of RCA concrete mixes with EMV mixes, similar to those of mixes made with NCA or RCA by the traditional mix proportioning method. It should be noted that previous studies on mixes made using the revised EMV method did not consider improvement in compressive strength.…”
Section: Experimental Programmentioning
confidence: 99%
“…It should be noted that all RCAs did not meet the specified Korean standards (KS) for concrete with respect to 2.5 as the specific gravity and 3.0% as water absorption, except for the 'RA' aggregate, which marginally satisfied the specific gravity standard with a value of 2.52 [35][36][37][38]. Previous studies have mainly focused on obtaining test results for the elastic modulus [5,8,12,13,27,28] and drying shrinkage [28][29][30] of RCA concrete mixes with EMV mixes, similar to those of mixes made with NCA or RCA by the traditional mix proportioning method. It should be noted that previous studies on mixes made using the revised EMV method did not consider improvement in compressive strength.…”
Section: Experimental Programmentioning
confidence: 99%
“…As the adhesive mortar content of RCA increased with the number of recycling cycles, the amount of cement, sand, and water required for unit concrete decreased in the order of R1, R2, and R3. A detailed description of the mix proportions of concrete designed with the EMV method can be found in our previous studies [ 23 , 24 ].…”
Section: Experimental Programmentioning
confidence: 99%
“…Figure 5 shows the relationship between the residual mortar content (RMC) on RA and the density and water absorption of RA investigated in other studies. There may be differences depending on production processes and the impurities contained in aggregates, in general, as the RMC increases, the specific gravity decreases and the water absorption rate tends to increase [3,13,33,35,36,[38][39][40][41][42][43][44].…”
Section: Recycled Aggregatementioning
confidence: 99%
“…As shown in the table, the mechanical properties of RAC using the EMV and M-EMV methods showed similar or higher values in comparison to conventional natural aggregate concrete. Yang et al [42] and Abbas et al [74] investigated EMV-based RAC and found it comparable to or superior than NAC in terms of durability as well as mechanical properties such as compressive strength and elastic modulus.…”
Section: R Rmc V Sg Sgmentioning
confidence: 99%